Overcoming the Achilles' heel of photodynamic therapy - Fan, Wenpei; Huang, Peng; Chen, Xiaoyuan (Chemical Society reviews, 2016)
Photodynamic therapy (PDT) has been applied to treat a wide range of medical conditions, including wet age-related macular degeneration psoriasis, atherosclerosis, viral infection and malignant cancers. However, the tissue penetration limitation of excitation light hinders the widespread clinical use of PDT. To overcome this "Achilles' heel", deep PDT, a novel type of phototherapy, has been developed for the efficient treatment of deep-seated diseases. Based on the different excitation sources, including near-infrared (NIR) light, X-ray radiation, and internal self-luminescence, a series of deep PDT techniques have been explored to demonstrate the advantages of deep cancer therapy over conventional PDT excited by ultraviolet-visible (UV-Vis) light. In particular, the featured applications of deep PDT, such as organelle-targeted deep PDT, hypoxic deep PDT and deep PDT-involved multimodal synergistic therapy are discussed. Finally, the future development and potential challenges of deep PDT are also elucidated for clinical translation. It is highly expected that deep PDT will be developed as a versatile, depth/oxygen-independent and minimally invasive strategy for treating a variety of malignant tumours at deep locations. This review summarizes the latest progress in deep photodynamic therapy (PDT), which overcomes the Achilles' heel of PDT.